Synthesis of Nanofiber from Polyvinyl Alcohol (PVA)-Collagen Using Electrospinning Methods - Sudirman Sudirman; Aloma Karo Karo; Sulistiyoso Giat Sukaryo; Karina Dwi Adistiana; Kiagus Dahlan (Research Center for Chemistry - LIPI, 2020)
Polyvinil alcohol (PVA) polymer can be used as matrix to be mixed with collagen in the subtance of primary wound dressing material to cover wound that prevents growth of bacteria and enhanced tissue formation. Collagen fiber is fragile, so important to combined with PVA to obtain better mechanical properties. The PVA-collagen fibers are prepared in aqueous solutions with PVA (10%) and collagen concentration (1% and 2%) using electrospinning method and the effect of voltage 15 kV, 19 kV, and 23 kV. Analysis of functional groups show that the presence of identical compounds produced and new functional groups are not formed. SEM data show that the effect of variation of voltage and collagen concentration on the resulting morphology of fiber. PVA-collagen 2% fibers produce continuous fibers, has a diameter 284-426 nm, thickness 0.0324-0.0483 mm and has a high percent of elongation so it can be used as a wound dressing material.